The Outpatient Forensic Substance Abuse Profile - Gianciulli, James M. (International journal of offender therapy and comparative criminology, 1993)
This study examines the reliability and validity of an instrument that is clinically useful for assessment of risk factors among chemically dependent populations in an outpatient forensic setting. It is reliable, both across time and internally, and demonstrates a high degree of user acceptance. There is good agreement between client scores and independent assessment of the same characteristics. Continued examination of the measure's ability to differentiate between forensic populations and substance abuse populations is needed